2017
DOI: 10.3892/ol.2017.5999
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase IIα and Ki67 are prognostic factors in patients with hepatocellular carcinoma

Abstract: The present study was designed to determine the significance of DNA topoisomerase IIa (TopoIIα) and Ki67 in hepatocellular carcinoma cells (HCCs). The present study included 353 patients with HCC. The association of clinicopathological data with the expression of TopoIIα and Ki67 by immunohistochemistry was analyzed by χ2 test. Cox multivariate proportional hazards regression analysis and Kaplan-Meier analysis were performed with all the variables to derive risk estimates associated with overall survival (OS)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Cell proliferation status is an important factor that reflects tumor biology and affects prognosis and treatment efficacy (5). Ki-67 protein, which is present in all phases of cell cycle (G 1 , S, G 2 and mitosis) except for resting cells (G 0 ), is an established marker suggestive of active cell proliferation (6).…”
Section: Introductionmentioning
confidence: 99%
“…Cell proliferation status is an important factor that reflects tumor biology and affects prognosis and treatment efficacy (5). Ki-67 protein, which is present in all phases of cell cycle (G 1 , S, G 2 and mitosis) except for resting cells (G 0 ), is an established marker suggestive of active cell proliferation (6).…”
Section: Introductionmentioning
confidence: 99%
“…Which was more importantly, the immunohistochemical results ( Fig 1C ) also showed that a negative correlation existed between SEPP1 and Ki67 expression. Since Ki67 was reported to be a traditional proliferation and differentiation index in numerous tumor [ 17 ], we demonstrated that the poor degree of differentiation, the lower expression of SEPP1. In addition, data (HTSeq-FRKM) from 374 of liver hepatocellular carcinoma (LIHC) cases and 50 of normal human were also obtained and analyzed by using the Cancer Genome Atlas Program (TCGA, https://www.cancer.gov/about-nci/organization/ccg/research/structural-genomics/tcga ) and R3.6.1.…”
Section: Resultsmentioning
confidence: 80%
“…These patients were evaluated from the day of surgical resection to the last day of follow-up (August 15, 2017), with a median follow-up time of 59 months (range, 2.0–128.0 months). Liver function and tumor differentiation were assessed by Child-Pugh classification ( 18 ) and the Edmondson grading system ( 18 ), respectively. Tumor stages were assessed according to the 2010 International Union Against Cancer Tumor-Node-Metastasis (TNM) classification system ( 19 ), and curative resection was defined as previously described ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Relapse-free survival (RFS) was defined as the interval between the date of surgery and the date of diagnosis of any type of relapse (intra-hepatic recurrence or extrahepatic metastasis). The inclusion criteria included the following: ECOG score ( 18 ) of 0–1 prior to surgery, absence of ascites, hepatic encephalopathy and any distant metastasis, only one tumor lesion and Child-Pugh class A. Clinicopathological data of the patients with HCC ( Table I ) were collected from the hospital database medical records. Survival information was obtained from medical records, telephone interviews and the Social Security Death Index ( 18 ), and all pathological data were pathological characteristics originally assessed by pathologists.…”
Section: Methodsmentioning
confidence: 99%